PENGEMBANGAN DAN VALIDASI SKALA KEBERSYUKURAN ISLAM (IGS-10) - Ahmad Rusdi; Sakinah Sakinah; Putri Nilam Bachry; Novia Anindhita; Muflihah Azahra Iska Hasibuan (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
There were not many adequate instruments to measure gratitude for the Indonesian people, especially the Muslim community. The purpose of this study is to develop the Islamic Gratitude Scale (IGS-10) by conducted an adequate set of tests. A total of 1218 respondents from students and workers participated on this study. This study found that the Islamic Gratitude Scale (IGS-10) has a good reliability (α= 0.863), good content validity and good factorial validity. The exploratory factor analysis found that IGS-10 has two factors, extrinsic gratitude (α= 0.845) and intrinsic gratitude (α= 0.761). Several sets of correlation tests found that IGS-10 has a good convergent validity, IGS-10 correlates with the Gratitude Questionerre (GQ-6), Gratitude Resentment and Appreciation Scale - Short Form (GRAT-SF), and gratitude toward God. Furthermore, IGS-10 correlated with Subjective Happiness Scale (SHS), Positive Affect and Negative Affect Schedule (PANAS), Multidimensional Body Self Relations Questionnaire - Appearance Scale (MBSRQ - US), and subjective well-being. This finding indicated that IGS-10 has a good cirterion-related validity. But unfortunately, IGS-10 did not correlate with Adolescents’ Self-concept Short Scale (ASCSS), optimism scale (LOT-R) and The Satisfaction with Life Scale (SWLS). IGS-10 was associated with Social Desirability Scale (SDS) with low correlation. To develop this scale the next process that can be done is norming, so that the IGS-10 will become a scale that can be used widely and more convincingly.